Simulation study of polymer flooding performance : Effect of salinity, polymer concentration in the Malay Basin - Mohd Syazwan, Mohd Musa; Agi, Augustine Aja; Nwaichi, Peter Ikechukwu; Norida, Ridzuan; Siti Qurratu’ Aini, Mahat (Elsevier B.V., 2023)
The major problem of the water flooding development process is the flood process's high mobility and viscous fingering. Previous studies have shown that polymer flooding is viable and can recover bypassed oil. However, the mechanism of the polymer flooding process is still tenuous in literature. Therefore, in this study, a two-dimensional model was used to simulate polymer flooding and forecast the mechanism of the polymer flood in the presence of electrolytes. Likewise, the effect of pH, pressure, and temperature on the polymer flooding process was investigated. Thereafter, the model was validated with an independent set of experimental data from the literature. The results show that the polymer flooding mobility ratio (M) was 0.36 indicating a favorable mobility control, thereby improving oil recovery by 60% of original oil in place (OOIP). In comparison, to water flooding mobility ratio of 3.6, which was greater than 1, thus resulted in viscous fingering, early water breakthrough, and oil recovery of 36% OOIP. Besides, at high salinity concentrations, the polymer adsorption was 3.3 mg/g compared to 2.2 mg/g from the experimental results. This indicates that the simulation results were consistent with the experimental results at the same concentration. Likewise, the simulation and experimental studies suggest high oil recovery was obtained at a higher injected pore volume. Finally, it can be concluded from this study that mechanical trapping and adsorption of the polymer on the pores of the porous media were the dominant mechanisms during the polymer flooding.